Legal Protection for Apartment Buyers in Relation to the Non-Fulfillment of Development Obligations (International Journal of Education and Literature, 2025)
In social life, buying and selling are fundamental mechanisms for transferring rights, beginning with an agreement. According to Articles 1313 and 1338 of the Indonesian Civil Code, agreements are legally binding acts with the force of law for the parties involved. One high-value transaction is the sale and purchase of apartment units, which involves developers as sellers. In practice, developers often fail to deliver units within the agreed timeframe. This study examines (1) the developer’s responsibility toward buyers when units are not delivered and (2) the legal protection available for buyers under such circumstances. The research applies Hans Kelsen’s Theory of Responsibility and Satjipto Rahardjo’s Theory of Legal Protection, using a normative juridical method based on library research. Primary, secondary, and tertiary legal materials were analyzed through statutory, conceptual, analytical, and case approaches, employing grammatical and systematic interpretation, legal analogy, and legal refinement. Findings reveal that developers are primarily responsible for delivering fully paid units. Failure to fulfill this obligation, due to breach of contract or negligence, triggers legal liability in the form of performance or compensation. Legal protection for buyers ensures their rights are safeguarded, and even in cases of developer negligence or bankruptcy, consumers are legally entitled to receive the apartment units they have purchased.